Prevalence of osteoarthritis knee among elderly in rural field practice area of Rajarajeswari Medical College, Bengaluru, India - S., Suriyan; S., Usha; M., Shashikala; C., Chandrakala (International Journal Of Community Medicine And Public Health, 2024)
Background: The most prevalent kind of arthritis and a highly common disease of the elderly is osteoarthritis (OA). It is a major contributor to disability among elders. The cervical and lumbosacral spine, the hip, the knee, and the first metatarsal phalangeal joint are the joints most frequently afflicted by it. Objective was to estimate the prevalence of osteoarthritis knee and to assess the risk factors associated with osteoarthritis knee among elderly persons in rural field practice area of Rajarajeswari Medical College, Bangalore. Methods: A cross-sectional study was conducted by visiting house to house among 150 elderly people selected by purposive sampling technique at Chunchunnakuppe village which is located on South Bangalore from June 2023 to July 2023. A detailed clinical examination of knee using American College of Rheumatology (ACR) criteria and Socio demographic information were also elicited. Results: A total of 150 elder respondents were interviewed out of which 63 (42%) had OA knee. Female gender, history of a knee injury, family history of knee pain, other chronic illness, current physical activity, BMI, and smoking status were found to be significantly associated with knee OA (p<0.05). Conclusions: In the study area, osteoarthritis of the knee was quite prevalent. Some of the modifiable factors like physical activity, smoking, BMI are significantly associated with OA knee.